Women's human rights : unfinished business - Gomez, Adriana (Latin American and Caribbean Women's Health Network SantiagoCL, 2003)
Offers a broad perspective on women's human rights, with an emphasis on sexual and reproductive rights and a special outlook on certain national contexts.